IMPLEMENTATION OF SPIRITUAL COMMUNICATION IN BUILDING THE MASJID PRENEUR MOVEMENT IN INDONESIA - al-Fikri, Muchsin; Matulessy, Delvin Musa Navaro (PT Altin Riset Publishing, 2024)
This research aims to understand the role of spiritual communication in building the Masjid Preneur movement in Indonesia, a movement that integrates Islamic spiritual values into mosque-based entrepreneurship development. A qualitative approach with a case study method was used in this study, with data collected through in-depth interviews, observations, and documentation from several mosques actively involved in entrepreneurial activities. The study highlights how spiritual communication delivered by religious leaders, such as imams and ustaz, has shaped a work ethic based on Islamic values such as honesty, hard work, and responsibility. The results indicate that spiritual communication plays a significant role in motivating the mosque community to engage in economic activities that not only pursue material gain but also social and spiritual well-being. However, several challenges were identified in implementing this movement, including religious leaders' limited knowledge of modern business practices and the generational gap among community members. This research concludes that the sustainability of the Masjid Preneur movement depends on the mosque's ability to adapt to the evolving needs of the community, particularly through collaboration with various stakeholders and the application of business practices relevant to current developments without compromising Islamic values. These findings provide insights into the importance of spiritual communication in supporting faith-based entrepreneurship within mosque environments.